A Pragmatic Analysis of Selected Newspapers’ Coverage of the Covid-19 Pandemic in Nigeria - ADEOTI , Oluwatomi (International Journal of Language and Literary Studies, 2023)
Language is a pivotal instrument in the hand of journalists; they manipulate language at their disposal for accomplishing numerous goals. Thus, this study explores a pragmatic investigation of how meanings are interpreted in the selected newspapers’ coverage of the Coronavirus Pandemic in Nigeria. Mey’s (2001) Pragmatic Acts Theory was used to analyze ten (10) data selected purposively from The Punch and The Vanguard Newspapers between February 2020 and June 2020. The study found out that the pragmatic relevance of the COVID-19 newspapers’ coverage is embedded in its media functions as it serves as an indicator to interpret the messages inherent in the coronavirus newspapers’ coverage and a pract of warning to the citizens of Nigeria to stay safe. The study also revealed that the practs used depend on context, situation and existing shared-knowledge of both the speaker and the reader. It was observed that journalists use the news headlines to perform several acts of warning, sensitising, informing, exposing, etc. to achieve different goals and pass numerous meanings to their listeners/readers during the COVID-19 Pandemic in Nigeria. Results indicated that the Nigerian media performed well in terms of covering the pandemic, which in turn created awareness. However, the coverage was not in-depth as most of the reported stories were short and were predominantly straight news. This paper concludes that journalists use contextual language to enhance social relations among the readers.